Single crystals of LnFeAsO1-xFx (Ln=La, Pr, Nd, Sm, Gd) and Ba1-xRbxFe2As2: growth, structure and superconducting properties - Karpinski, J. (2009)
Fil: Fasano, Y. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; University of Geneva; Suiza